Complete Rectal Prolapse. Case presentation - José Antonio Feliu Rosa; Jorge Luis Estepa Pérez; Tahiluma Santana Pedraza; Lianet González Gutiérrez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Rectal prolapse is the invagination of rectal layers through the anal canal and its protrusion out of it. Its incidence is 2.5 per 100 000 inhabitants with a predominance of elderly women. It is a little known, chronic condition of benign course, whose clinical and endoscopic presentation is so variable that it can be confused with other entities such as a colorectal cancer or ulcerative colitis. For these reasons a case of complete rectal prolapse in an adult male patient is presented. The surgical management performed is discussed.